Diversity of moth ( Order: Lepidoptera ) at R.E.A.C.H Biodiversity Centre Forest, Cameron Highland. - Nursyahirah Zakaria (2017)
R.E.A.C.H Biodiversity Centre Forest is a 16 years old rehabilated forest. Local farmers have cleared the site for agricultural and vegetation activities. The site is currently managed by Regional Environmental Awareness Cameron Highland (R.E.A.C.H), a NGO with the help of volunteers through reforestation programme in order to attract back the old diversity of animals. A study of moth fauna was conducted at R.E.A.C.H Biodiversity Centre Forest in Cameron Highland from July to August in 2016 aimed to determine the diversity of the moth fauna and to construct a pictorial identification key to the families of moth species recorded at the centre for usage of general and non-taxonomist. A total of 89 individuals of moths comprising of 53 species belonging to 10 families were recorded in 24 day of sampling by using light traps. Families Arctiidae (3 species), Bombycidae (1 species), Drepanidae (1 species), Erebidae (2 species), Geometridae (21 species), Noctuiidae (13 species), Nolidae (1 species), Saturniidae (2 species), Sphingidae (1 species) and Uraniidae (1 species) were identified in this study. The most dominant family recorded here is Geometridae and Noctuiidae among the other families. The overall Shannon-Wiener index (H’) value for 24 days sampling is 3.38 (stable environmental condition) while (H’max) is 3.97, Pielou’s Evennes index (J) is 0.85 and Margalef index (DMg) is 11.58. The values of H’, J and DMg indices show that R.E.A.C.H Biodiversity Centre Forest, Cameron Highland has moderately large diversity of moth species with uniform distribution. A pictorial identification key was constructed for 10 families species of moth by referring their morphology characteristics. Moth plays an important role in determining ecosystem of Cameron Highland. Further studies should be conducted on the secondary forests to study about diversity of habitat before and after disturbing forest as it is still deficit especially in Peninsular Malaysia.